Separation, Purification, and Characterization of Analogues Components of a Commercial Sample of New Fuchsin - Montes de Oca, María Noel (2010)
New Fuchsin (NF), also known as Magenta III, has potential applications in photodynamic therapy. The commercial product labeled NF contains two other dye components in different proportions, Magenta II and Magenta I (Rosaniline). The proportions of NF, Magenta II, and Magenta I determined by reversed-phase high-performance liquid chromatography (RP-HPLC) in the commercial sample used were 71.6 +/- 0.4%, 25.2 +/- 0.2%, and 2.8 +/- 0.1% (n = 7), respectively. The isolation, purification, and characterization of commercial NF dye components were carried out applying different techniques, such as preparative column liquid chromatography (PCLC), thin layer chromatography (TLC), RP-HPLC, absorption spectrophotometry, nuclear magnetic resonance spectroscopy (NMR), electrospray ionization mass spectrometry (ESI-MS), and tandem electrospray ionization mass spectrometry (ESI-MS-MS). After separation and isolation, the degree of purity obtained for NF compound was higher than 95% and 92% for Magenta II and Magenta I compounds, respectively. Therefore, it is essential to ensure a high degree of purity of these dyes as raw material to obtain new drugs intended for therapeutic treatments.